Asia-Pacific Population and Development Report 2023 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2023)
This report, prepared for the Seventh Asian and Pacific Population Conference, in 2023, brings together the latest statistical evidence on the priority actions of APMD, with a particular focus on SDG indicators, good practices and lessons learned by member States and civil society organizations, based on responses to the voluntary national survey and research findings on key population and development issues. The report also provides specific forward-looking recommendations to guide the continuing implementation of APMD and the Programme of Action in Asia and the Pacific. This report is intended as a resource and guide to support countries in the region in developing future inclusive and sustainable population and development policies.